Biometrics ‐ market segments and applications - Költzsch, Gregor (Journal of Business Economics and Management, 2007)
Biometric methods are concerned with the measurement and evaluation of human physiological or behavioral characteristics. During the last years, the economic relevance of the biometric industry and market has increased rapidly. Although public security projects have initiated the positive market development, future growth will be also generated by private sector demand such as secure and convenient banking, payment applications etc. The deployment of biometrics to machine readable travel documents such as passports provides citizens with first experiences in biometric applications, thereby functioning as pioneer projects and market openers for other market segments. For example, biometric passports will redefine the border control process in the future, and in the midterm, aviation security is another market segment that will contribute to the growth. To prepare for this business, the industry must carefully analyze the market and meet the demand. This article assesses the economic relevance of biometrics and discusses selected market segments. First Published Online: 14 Oct 2010